Technologies of Care: Robot Caregivers in Science and Fiction - Silvana Colella (Humanities, 2023)
In the field of elderly care, robot caregivers are garnering increased attention. This article discusses the robotisation of care from a dual perspective. The first part presents an overview of recent scholarship on the use of robots in eldercare, focusing mostly on scientific evidence about the responses of older adults and caregivers. The second part turns to narrative evidence, providing a close reading of Andromeda Romano-Lax’s Plum Rains (2018), a speculative novel set in Japan in 2029, which explores the implications—ethical, affective, social—of communities of care that include non-human agents. My argument is twofold: (1) although science and fiction operate according to different models of knowledge production, considering narrative insights alongside scientific ones can enlarge our understanding of the complexities of robotic care; (2) hitherto overlooked in literary studies, Plum Rains deserves attention for its nuanced representation of a hybrid model of care, which does not discard robotic assistance on the basis of humanist arguments, nor does it endorse techno-solutionism, reminding readers that the fantasy of robots that care is fuelled by the reality of devalued human care work.